REPRESENTASI KONSTRUK PEREMPUAN DALAM SYAIR TUKHOTIBUL MAR’AH AL-MISRIYAH KARYA AL-BADIYAH - Dyo Rusna; Wanda Choirunisa; Rohanda Rohanda (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
The purpose of this study is to discover the image of women constructed in the poem Tukhotibul Mar'ah Al-misriyah by Al-badiyah. The method used in this study is qualitative with data analysis techniques using hermeneutics to discover the meaning behind the poem Tukhotibul Mar'ah Al-misriyah by Al-badiyah. The data source for this study is the book Mahfudzat, published by Pondok Modern Darussalam Gontor in Ponorogo 1416 H. The data in this study are verses from the poem Tukhotibul Mar'ah Al-misriyah by Al-badiyah that contain constructions of women. The theory used in this study is feminist literary criticism with Amina Wadud's theory. The results of the study show that the poem Tukhotibul Mar'ah Al-misriyah by Al-badiyah constructs women's clothing and manners, whereby women should not be excessive when in public and should dress simply and cleanly. This poem also represents that women who wear the veil may remove it when they are with their families. In addition, women who wear the hijab are constructed as symbols of beauty and purity. This poem constructs women as symbols of purity, beauty, and elegance in society.